The Analysis of Language Variation used in Interaction Among a Teacher and Students in the Teaching- Learning Processes of Reading - Helmie, Jauhar; Nurviyani, vina; sugih, Arief (PT. Impola Toba Lendt, 2024)
This research was aimed at finding and describing the analysis of language variation used in interaction among teacher and students in teaching and learning process of reading in 8th class at SMP Negeri 1 Sukaresmi-Cianjur. The research was conducted three meetings in three different classes. It was a descriptive qualitative research with a naturalistic approach. The setting of the research was SMP Negeri 1 Sukaresmi-Cianjur. The methods of collecting the data were questionnaire, observation and interview. The data were in the form of words and sentences of language variations and language styles. They included classroom observations, questionnaire and interview transcripts. The respondents were the English teacher and 8th students class at SMP Negeri 1 Sukaresmi-Cianjur. In reference to data analysis, the results show that the language variation used in interaction among the teacher and the students are divided into two kinds of language variations, i.e., (1) Register (2) Idiom. Moreover, the language style used in interaction among teacher and students were divided into four kinds of language styles, i.e., (1) Formal style, (2) Consultative style, (3) Casual style, (4) Intimate style. Implementing the language variations and language styles in teaching-learning processes of reading makes students easier to learn English particularly reading comprehension.